(In)Effectiveness of the Act on prevention of domestic violence in the Republic of Serbia - Jugović, Sreten M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
In the first part, the paper points to general nomotechnical omissions of the lawmaker. Next, it analyses the most important provisions of the Act, such as those concerning the immediate threat of domestic violence within the meaning of the Act. Central part of the paper deals with legislative novelties pertaining to police conduct, with special reference to the provisions on urgent measures whose issuance the Act on Prevention of Domestic Violence vests in the police. It thereby points to the flawed formulation by professional legislative drafters of the provisions on risk assessment, detention, and ones relating to the order imposing urgent measures. Additionally, it touches upon the issues of judicial protection against domestic violence. As a special problem, the author emphasizes (in the Conclusion) the absence of effective misdemeanour liability for the perpetrator of domestic violence, which could be solved by de lege ferenda amendments to the analysed Act, the Public Order and Peace Act and Misdemeanour Act.